Second Treatise of Government - Locke, John, 1632-1704 (Salt Lake City, UT : Project Gutenberg, 2005)
"Second Treatise of Government" by John Locke is a political philosophy work published in 1689. Writing anonymously during England's turbulent revolution, Locke outlines a radical vision of society founded on natural rights and government by consent rather than divine authority. His ideas challenge the established order, arguing that legitimate power flows from the people, not kings claiming God-given rule. This foundational text of liberal political theory emerged from dangerous conspiracies and exile, so controversial that Locke never acknowledged authorship during his lifetime. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Two_Treatises_of_Government
Release date is 2005-01-01
Dave Gowan and Chuck Greif
Keywords: Political science -- Early works to 1800; Toleration -- Early works to 1800; Liberty -- Early works to 1800